Answer:
10
Step-by-step explanation:
This is the answer because:
1) First, insert all the numbers into the expression
Expression: I -2(2) + -3(2) I
2) Next, do -2 x 2 and -3 x 2
-2 x 2 = -4
-3 x 2 = -6
3) Then, do -4 + -6
-4 + -6 = -10
4) Finally, the absolute value of -10 is 10
Therefore the answer is 10
Hope this helps!
Answer:
65
Step-by-step explanation:
(4-7i)(4+7i) =16 + 28i-28i -49i^2 ➡16 - 49i^2
16 + 49 = 65
the fault here is i^2= -1 and -1 multiplied by -49 is +49 not -49
A is the answer because its right according to the chart
A' (1,4)
B' (5,8)
C' (5,4)
D' (4,2)
The answer I get
8=24
No solution